From physical self-esteem to sports participation: The mediating role of exercise motivation and social support in adolescents. - Bo Peng; Weisong Chen; Hongshen Wang; Ting Yu (PLoS ONE)
Objective This study examines the mechanisms linking physical self-esteem to adolescents' sports participation, emphasizing the mediating roles of exercise motivation and social support. It aims to establish a comprehensive framework that integrates psychological and social factors to understand sports behavior among adolescents. Method A total of 2,588 adolescents from various regions in China were surveyed using validated scales for physical self-esteem, exercise motivation, social support, and sports participation. Structural equation modeling (SEM) was used to assess direct, mediated, and sequential mediation effects. Results The analysis confirmed that physical self-esteem significantly predicts sports participation directly (β = 0.094, p < 0.001). Exercise motivation and social support act as mediators, explaining 33.26% and 16.74% of the total effect, respectively. Sequential mediation analysis showed that physical self-esteem influences sports participation through the combined effects of exercise motivation and social support, contributing 29.61% to the total effect. Demographic analyses revealed that males, rural adolescents, and middle school students exhibit higher levels of self-esteem, motivation, and sports participation. Group differences were analyzed based on demographic variables, including gender, grade level, and family location. Conclusion This study underscores the critical roles of psychological traits and social contexts in shaping adolescents' sports participation. By revealing the mediating and sequential mediation effects of exercise motivation and social support, the research highlights pathways for targeted interventions. Schools and communities should focus on enhancing physical self-esteem and fostering supportive social networks to encourage sports participation. Future studies should incorporate longitudinal designs and explore cultural and regional variations to extend these findings.